Skrining Fitokimia dan Uji Aktivitas Antioksidan Jamur AS-3 yang Diisolasi dari Akar Sambiloto: Phytochemical Screening and Antioxidant Activity of Fungus AS-3 Isolated from The Root of Sambiloto - Sagia, Randi; Riga, Riga; Dewita, Febby Octavia; Yuranda, Fitri; Agustini, Dewi Meliati (Jurnal Sumberdaya Hayati, 2025)
Sambiloto, often referred to as the “Raja Pahit”, is a plant belonging to the Acanthaceae family. This plant is known to produce secondary metabolite compounds with various biological benefits, including antioxidant properties. Antioxidant compounds have been shown to counteract the formation of free radicals that are harmful to the body. The antioxidant activity of the Sambiloto plant can be evaluated using endophytic fungi associated with it. This study aimed to identify secondary metabolite compounds and evaluate the antioxidant activity of AS-3 Fungus isolated from the Sambiloto roots. Phytochemical analysis revealed that the ethyl acetate extract of AS-3 contained terpenoids, flavonoids, and alkaloids. In addition, the antioxidant activity test showed promising results, with an IC50 value of 10.225 ppm, indicating high antioxidant potential. This is the first report on the phytochemical screening and antioxidant activity test of the ethyl acetate extract of AS-3 fungus isolated from Sambiloto roots.